IMPLEMENTASI TQM DALAM PENGELOLAAN ZAKAT DI KOTA MALANG - Sri Eko Ayu Indrawati, Sudirman, (Fakultas Syariah, 2011)
Muslim community awareness on performing zakat (alms) rises in line with social economic life development of the community. A number of alms organizations compete to design activities to attract people and to propose more professional and transparent management. Particularly in Malang, there are several alms institution branches which have national reputation such as Yayasan Dana Sosial al-Falah (YDSF) and Baitul Mal Hidayatullah (bMh). In relation with alms management, this research raises the on integrated quality management in alms management. Integrated quality management in this research refers to Total Quality Management. This research focuses on the application of TQM principles at yDSF and bMh. both institutions are compared in terms of several aspects covering their innovation in satisfying customers, those who give the alms, people who are illegible to get alms, and people within the management (amil). The result, the model of alms management in both institutions are the appropriate management for alms management especially in Malang. Kesadaran umat islam akan kewajiban menunaikan zakat semakin meningkat seiring dengan taraf kehidupan sosial ekonomi umat yang berkembang pesat. Sejumlah lembaga zakat berlomba merancang kegiatan untuk menarik muzakki dan menawarkan pengelolaan yang lebih profesional dan transparan. Khusus di kota Malang, telah berdiri cabang- cabang lembaga zakat yang memiliki reputasi nasional, seperti Yayasan Dana Sosial al- Falah (yDSF) dan baitul Mal hidayatullah (bMh). Berkaitan dengan manajemen zakat, penelitian ini mengangkat isu tentang manajemen mutu terpadu dalam pengelolaan zakat. Manajemen mutu terpadu dalam penelitian ini disebut Total Quality Management. Penelitian ini melihat aplikasi prinsip-prinsip TQM di YDSF dan BMH. Kedua lembaga tersebut diperbandingkan dalam beberapa unsur antara lain inovasi mereka dalam rangka memuaskan pelanggan yang dalam hal ini muzakki, mustahiq, dan amil. Model pengelolaan zakat di kedua lembaga tersebut merupakan gambaran tentang manajemen yang tepat untuk pengelolaan zakat, khususnya di Kota Malang.